Profile communautaire jeunes et aînés : Populations anglophones Gaspé - Vision Gaspé-Percé Now (2016)
Ce document est une ressource pour les organismes communautaires et gouvernementaux et pour ceux qui peuvent bénéficier de l’information visant les aînés et les jeunes anglophones de Gaspé. La production du document est possible grâce au soutien financier de Santé Canada. Les données démographiques ont été fournies par le Réseau communautaire de santé et des services sociaux (RCSSS).

The Build - Richardson, Mary (Council for Magdalen Islanders (CAMI), 2015)
This case study presents a project being implemented in the Baiedes-Chaleurs, Quebec, by which a group of elementary and high school students are building a sailboat with a teacher. They have the support of a broad range of community, institutional and non-for-profit partners who believe, like them, that a challenging project can have positive outcomes both inside and outside the classroom.